2013
DOI: 10.1186/1471-2202-14-19
|View full text |Cite
|
Sign up to set email alerts
|

Absence of CCR5 increases neutrophil recruitment in severe herpetic encephalitis

Abstract: BackgroundThe neuroinflammatory response aimed at clearance of herpes simplex virus-1 (HSV-1) plays a key role in the pathogenesis of neuroaxonal damage in herpetic encephalitis. Leukocytes activated in an adaptive immune response access brain tissue by passing through the blood–brain barrier. The chemokine CCL5/RANTES is involved in recruitment of these cells to the brain acting via the receptors CCR1, CCR3 and mainly CCR5. Here, we evaluated the role of CCR5 on traffic of leukocytes in the brain microvascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Among herpes viruses, herpes simplex viruses (HSV-1, -2) are neurotropic viruses that cause encephalitis in newborns and immunocompromised humans. CCL5 was shown to be produced during herpetic encephalitis in mice and mediate T cell recruitment to the CNS [82]. Other reports demonstrate that CCL5 is upregulated in latently infected trigeminal ganglia, a major feature of HSV-1 infection, which results in the retention of T lymphocytes in neurons of both mice and humans and prevents viral reactivation [83].…”
Section: Neurotropic Infectionsmentioning
confidence: 99%
“…Among herpes viruses, herpes simplex viruses (HSV-1, -2) are neurotropic viruses that cause encephalitis in newborns and immunocompromised humans. CCL5 was shown to be produced during herpetic encephalitis in mice and mediate T cell recruitment to the CNS [82]. Other reports demonstrate that CCL5 is upregulated in latently infected trigeminal ganglia, a major feature of HSV-1 infection, which results in the retention of T lymphocytes in neurons of both mice and humans and prevents viral reactivation [83].…”
Section: Neurotropic Infectionsmentioning
confidence: 99%
“…We have also demonstrated that chemokine-driven leukocyte recruitment into the brain of HSV-1 infected mice was associated with infectious outcome (Vilela et al 2008;Vilela et al 2009, Vilela et al 2010Vilela et al 2013).…”
Section: Discussionmentioning
confidence: 91%
“…Mice were treated with 0.2 mg trimethoprim and 1 mg sulfamethoxazole (SEPTRA, GlaxoSmithKline, Mississauga, Ontario, Canada) per mL of sterile water ad libitum started 1 week before and maintained for 2 weeks after transplantation. WT and CCR2 -/recipient mice were exposed to 10 Gy total body irradiation using a 60 Co source (Theratron-780; MDS Analytical Technologies, Concord, Ontario, Canada). Bone marrow cells from age-and sex-matched WT and CCR2 -/donor mice were aseptically harvested by flushing the femurs and tibias with Dulbecco's phosphate-buffered saline (DPBS) containing 1 g/L glucose and 36 mg/L sodium pyruvate and supplemented with 2% fetal bovine serum (FBS; Wisent, St-Bruno, Quebec, Canada).…”
Section: Irradiation and Bone Marrow Transplantationmentioning
confidence: 99%
“…In this respect, the increased mortality rates observed in CCR2-deficient mice and when deficiency affects hematopoietic cells, were associated with elevated inflammatory cytokines (IL-1β and IL-6) and chemokines (CCL2, CCL3 and CCL5) production in the brain compared to WT. Indeed, it has been already reported that chemokine receptors deficiency may result in increased inflammatory cytokines and chemokines production during CNS insults, which could increase brain damages as well as lethality [16,17,44,60]. Furthermore, the excessive production of chemokines, such as CCL2, CCL3 and CCL5, observed in the more susceptible groups could induce the recruitment of peripheral immune cells such as natural killer (NK) cells and T cells that in turn may contribute to amplify the global inflammation triggered by the virally-infected cells [11].…”
Section: Fig 6 Effects Of Ccr2 Deficiency In Resident Cells Of the Cmentioning
confidence: 99%